2015
DOI: 10.1007/s12665-015-4128-x
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of a deep-seated landslide in central Taiwan

Abstract: The unstable slope, which is located at Lushan, central Taiwan, slid when heavy rainfall occurred in recent decades, posing a threat to a nearby village. Slope stability analysis in three dimensions is more realistic and can advance comprehension of the sliding mechanism. The landslides caused by two heavy rainfall events are simulated in sequence using finite element modeling. The three-dimensional (3D) modeling is established according to the data of extensive investigations, including field reconnaissance, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Benefiting from the rapid development of computer techniques, numerical software with function of three-dimensional (3D) model has become a more powerful tool to investigate slope instability problems. Compared to the 2D model that can only demonstrate horizontal or vertical sections, 3D numerical modelling is able to give more realistic results and conduct more comprehensive analysis of sliding mechanism, especially in such a case with non-uniform resistance distribution [16,17]. In addition, 3D model simulation enables better 3D visualization and details such as estimated sliding volume.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Benefiting from the rapid development of computer techniques, numerical software with function of three-dimensional (3D) model has become a more powerful tool to investigate slope instability problems. Compared to the 2D model that can only demonstrate horizontal or vertical sections, 3D numerical modelling is able to give more realistic results and conduct more comprehensive analysis of sliding mechanism, especially in such a case with non-uniform resistance distribution [16,17]. In addition, 3D model simulation enables better 3D visualization and details such as estimated sliding volume.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 3D model simulation enables better 3D visualization and details such as estimated sliding volume. From [16], their 3D analyses revealed the features that cannot be obtained in 2D analyses; for example, the sliding surface was not symmetric with the steeper portion on the east side, and the displacements around the boundary fractures were somewhat smaller than those in the middle portion. 3D model is more capable of presenting the full geometry and structures inside and outside of a slope, so it can better interpret the correlation between slope stability and its surroundings.…”
Section: Introductionmentioning
confidence: 99%
“…It is also observed that climate change and landslide activities have some significant relationship (Sewell et al, 2015). Some recent studies have revealed that submarine landslides and turbidity currents may become more likely due to future rapid global warming (Chang and Huang, 2015). However, some research have indicated that rapid climate change does not necessarily increase the current activity, and thus do not provide a direct evidence as a primary triggering factor (Clare et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The bedrock of the slope mass is mainly composed of slate with strikes of cleavage range from N10° to 40°E. The slope is defined as composed of 20-m-thick colluvium near the surface and fresh slate at bottom [24]. The Lushan formation in the area belongs to the attitude of the foliation, which influences the mass rock creep structures of foliated rocks and may experience deformation by potential landslides [25].…”
Section: Principle Of the Tdr Monitoring In Landslide Areasmentioning
confidence: 99%